The psychology of selling - Tracy, Brian (Gildan, 2013)
Brian Tracy, one of the top professional speakers and sales trainers in the world today, found that his most important breakthrough in selling was the discovery that it is the "Psychology of Selling" that is more important than the techniques and methods of selling. Tracy's classic audio program, The Psychology of Selling, is the best-selling sales training program in history and is now available in expanded and updated audiobook format for the first time. Salespeople will learn: "the inner game of selling" how to eliminate the fear of rejection and how to build unshakeable self-confidence. Salespeople, says Tracy, must learn to control their thoughts, feelings, and actions to make themselves more effective.